INTERNAL CONTROL PRACTICES OF MOSQUES IN JAVA, INDONESIA - Islamiyah, Nining; Siraj, Siti Alawiah; Osman, Ahmad Zamri (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
Internal controls are necessary tools to help organizations attain their organizational goals. Lack of these controls in any type of organizations could lead to fraudulent activities, which consequently may hamper the achievement of organizational goals. This study aims to investigate the internal control practices in two Indonesian mosques; Mosque A and Mosque B. The study employed the Committee of Sponsoring Organization (COSO 2013) framework of internal controls to frame the investigation of internal control practices in these two mosques. Data collection was undertaken through interviews and reviews of relevant documents. The findings revealed that the two selected mosques, Mosque A and Mosque B, have the five internal control practices in place. These include control environment, risk assessment, control activities, information and communication, and monitoring activities. This study concludes that internal control practices are a necessary process to support the accountability of the mosque. The results may be used as a potential reference for improving internal control practices in the Indonesian mosques.